2023
DOI: 10.3390/nu15163649
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effects of Short-Term Daily Intake of Nitraria retusa Tea on Lipid Profile: A Pre-Post, Uncontrolled Pilot Study in Both Healthy and Overweight/Obese Adults

Aicha Laouani,
Hana Nasrallah,
Awatef Sassi
et al.

Abstract: In the present study, we aimed to explore the feasibility, compliance, and potential benefits of Nitraria retusa extract (NRE) intervention in both healthy (BMI ≤ 24.9 Kg/m2) and overweight/obese adults (BMI > 25 Kg/m2). A total of 98 participants, including 37 healthy individuals and 61 overweight/obese adults, were randomly assigned to either a low-dose (500 mg/day) or a high-dose (2000 mg/day) NRE intervention group. Plasma lipid biomarkers, liver and kidney functions, general hematology, and blood gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…However, the aforementioned study used only two cups (8oz) of herbal infusion and lasted only 6 days, whereas our study used a higher dose (1500 mg) of S. scardica extract and lasted 28 days. Moreover, other studies on other plant-derived extracts such as Nitaria retusa and green tea extract supplementation failed to positively affect liver function in healthy subjects [47,50], corroborating the superior efficiency of SidTea+ TM extract in regulating liver function in apparently healthy individuals. Nonetheless, it should be noted that different extracts, doses and consumption duration could be determining factors for the different results observed between the studies.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…However, the aforementioned study used only two cups (8oz) of herbal infusion and lasted only 6 days, whereas our study used a higher dose (1500 mg) of S. scardica extract and lasted 28 days. Moreover, other studies on other plant-derived extracts such as Nitaria retusa and green tea extract supplementation failed to positively affect liver function in healthy subjects [47,50], corroborating the superior efficiency of SidTea+ TM extract in regulating liver function in apparently healthy individuals. Nonetheless, it should be noted that different extracts, doses and consumption duration could be determining factors for the different results observed between the studies.…”
Section: Discussionsupporting
confidence: 54%
“…These results are partly verified in a study by Kassi et al [ 20 ] which showed that S. euboea extract supplementation (another Sideritis species) reduced total cholesterol levels but failed to elicit any other effect on the lipidemic and inflammatory status of humans. In another study, Nitaria retusa extract did not affect the lipidemic profile of healthy participants but induced a significant reduction in triglycerides levels and an increase in HDL cholesterol in the obese participants [ 47 ]. In the present study, no significant changes were detected in the levels of creatinine, uric acid, bilirubin, lactate dehydrogenase and SGOT.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative and quantitative analyses of NRE were performed using a confirmed high-performance liquid chromatography (HPLC) method (UHPLC-DAD, SHIMADZU 8045). The administered dose, containing 20 mg of flavonoids and 16 µg of isorhamnetin, was selected as previously described [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Our recent clinical trial has shown the safety and tolerability of Nitraria retusa tea in both healthy and overweight/obese individuals for ten days. We further demonstrated its potent hypolipidemic effect through the regulation of HDL and TG after short daily administration intake in overweight and obese participants with a dependent dose effect [ 38 ]. These interesting data prompted us to assess the weight-loss-promoting efficacy of Nitraria retusa in overweight/obese subjects in a double-blind placebo-controlled study.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Artemisia annua [ 18 ], Artemisia campestris [ 19 ], and Artemisia princeps [ 20 ] were all suggested to possess anti-obesity effects by inhibiting adipogenesis. Apart from these species, several other halophytes, such as Nitraria retusa [ 21 ], Adenocaulon himalaicum [ 22 ], and Limonium tetragonum [ 23 , 24 ], also showed anti-obesity potential, specifically by acting on the differentiation of adipocytes.…”
Section: Introductionmentioning
confidence: 99%